Ecopedagogical Values in Traditional Idiomatics - Yayat Sudaryat; Nurhadi, Jatmika (International Journal of Language and Culture, 2024)
The facts show that Nusantara (Indonesia) culture keeps a lot of local wisdom values. One of the cultural forms of Nusantara culture owned by Sundanese people is traditional expression. In the Sundanese language, traditional expression implied eco-pedagogical values. This research will comprehensively expose the eco-pedagogic values in the traditional Sundanese expression. This research used descriptive method and documentation technique or bibliographical study. The data was analyzed by immediate constituent analysis and hermeneutic analysis techniques. This research data is a number of traditional idiomatic Sundanese languages containing eco-pedagogical value. The result of the research showed that Sundanese traditional idiomatic contained eco-pedagogical values that can be used as the basis for local wisdom. The value of eco-pedagogic refers to real-life values based on the natural environment perspective. The eco-pedagogical aspect refers to the natural environment, flora, and fauna. So, this suggests that traditional idiomatics contain words that relate to nature, flora and fauna. For example, humans should not be separated from nature (Lamun diarah supana, kudu dipiara catangna). From time to time human civilization evolves from dependening on the nature stage (Bisa ngindung ka usum ngabapa ka jaman), managing the nature stage, to controlling the nature stage (Bisa ngigelan jeung ngigelkeun jaman). The ecopedagogical values which become the repertoire of local wisdom refers to the natural environment, time, flora, and fauna education.